FINISHING KAYU DARI BAHAN ALAM - ., Nofrial (CORAK, 2012)
Finishingis thefinal stageofthe workprocess of makingwoodproducts, includingthe provision ofcertain materials, toembellish, visuallyhighlightandprotectthe wood surface. Wood productswouldbemore attractivewhenfinished totheright. Realizean attractiveappearancefinishingsomething veryimportant, therefore there is need fora new discoveryforwoodfinishingmaterials. Herbsasa naturalmaterialpotentialforwoodproductsfinishingmaterials. In addition tofriendlyenvironment,plantsare alsoeasy to obtain. Plantsofvarioustypescan be processed andused as awoodfinishingmaterial, either as abasicdye, a mixture ofdyes, as wellasthe finalfinishing. In these experimentsconducted onturmeric, gum gambier, betel leaves,stickshenna, mangosteenrind, skinjengkol, andinjetforcoloringwood. Throughexperimental research, with thewettechniqueandthe resultsindicatesapgambiersaffroncolor the best, producingthe yellow colorof turmeric, gambierandinjetsapproducesa redcolormaroon. The maximumcoloris producedin addition to thebasicmaterialcontainingpigmentis good, as wellasprecisematerials processingtechniques, as well asabsorptionof thepigmentsare alsogoodtimber. Meanwhile,the colorproducedbybetel leaves, stickshenna, mangosteenrind, skinjengkol, less than the maximum. It isbased on theassumptionof researchersdue tolack/incompatibilityprocessingtechniquessuch materials. Keywords: finishing, wood, naturalmaterials.